Risk Assessment Considerations for Genetically Modified RNAi Plants: EFSA’s Activities and Perspective - Nikoletta Papadopoulou; Yann Devos; Fernando Álvarez-Alfageme; Anna Lanzoni; Elisabeth Waigmann (Frontiers in Plant Science, 2020)
Genetically modified plants (GMPs) intended for market release can be designed to induce “gene silencing” through RNA interference (RNAi). The European Food Safety Authority (EFSA) and other international risk assessment bodies/regulatory agencies have taken several actions to determine whether the existing risk assessment approaches for GMPs are appropriate for the risk assessment of RNAi-based GMPs or require complementary or alternative approaches. To our knowledge, at the international level, no dedicated guidelines have been developed for the risk assessment and regulation of RNAi-based GMPs, confirming that existing science-based risk assessment approaches for GMPs are generally considered suitable for RNAi-based GMPs. However, some specificities have been identified for the risk assessment of RNAi-based GMPs. Here, we report on some of these specificities as identified and addressed by the EFSA GMO Panel for the molecular characterisation, food/feed safety assessment and environmental risk assessment of RNAi-based GMPs, using the DvSnf7 dsRNA-expressing maize MON87411 as a case study.